2020
DOI: 10.1097/pec.0000000000001978
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Accuracy of Procalcitonin and Traditional Biomarkers in Pediatric Acute Musculoskeletal Infection

Abstract: Objectives: Septic arthritis (SA) is responsible for 20% of pediatric musculoskeletal infections (MSKI) and can have significant consequences. Early detection of SA is critical, and procalcitonin (PCT) has emerged as a promising biomarker. This study assessed the test performance of PCT and traditional biomarkers for suspected SA. Methods:We conducted a prospective study at two pediatric emergency departments (ED). Data collected measured serum levels of C-reactive protein (CRP), erythrocyte sedimentation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“… 17 Comparatively, CRP typically begins to elevate within 6 h of a stimulus and peak later than PCT, between 24 and 72 h. 17 McMichael et al reported that PCT, CRP, and erythrocyte sedimentation rate (ESR) performed reasonably well for the detection of MSKI, while WBC count was not predictive of MSKI. 18 Woo et al also confirmed that CRP and PCT had better predictive function for sepsis than WBC count. 19 In a multicenter trial, sepsis patients received either PCT-guided discontinuation of antimicrobials or standard of care.…”
Section: Discussionmentioning
confidence: 91%
“… 17 Comparatively, CRP typically begins to elevate within 6 h of a stimulus and peak later than PCT, between 24 and 72 h. 17 McMichael et al reported that PCT, CRP, and erythrocyte sedimentation rate (ESR) performed reasonably well for the detection of MSKI, while WBC count was not predictive of MSKI. 18 Woo et al also confirmed that CRP and PCT had better predictive function for sepsis than WBC count. 19 In a multicenter trial, sepsis patients received either PCT-guided discontinuation of antimicrobials or standard of care.…”
Section: Discussionmentioning
confidence: 91%
“…Another limitation is our retrospective classification of MSKI, which is why we used 2 physician raters to determine the diagnosis of patients included in the original study. 7 A strength of our study is that it is one of the first to evaluate the utility of the Kocher and Caird to detect MSKI in medium or large joints beyond the hip or knee joint. Although the Kocher and Caird are applied to all joints with monoarticular pain in clinical settings, there has been no evidence to support this application.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of enrollment and outcome classification are described in greater detail in our original study. 7…”
Section: Outcomementioning
confidence: 99%
“…If PCT normalizes faster than CRP, trending PCT instead of CRP could be cost saving in the long term because fewer tests would be needed. A recent study demonstrated that CRP outperformed PCT in diagnosing pediatric musculoskeletal infection, so measurement of PCT alone on initial evaluation may not be sufficient [14]. Another possible use for PCT is in reducing the duration of antibiotic courses for non-critical bacterial infections or facilitating earlier conversion from intravenous to oral antibiotics, although more research is needed on this topic before recommendations to support this clinical application can be made.…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer data to support the use of PCT use in meningitis or in infectious complications of trauma, burns and pancreatitis [11]. Recent studies have evaluated the role of PCT in identifying bacterial infection in children with pneumonia, musculoskeletal infection, central line and fever and urinary tract infections, with varying utility of PCT to predict bacterial vs. non-bacterial infection [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%